An Investigation of Fluid Flow Simulation in Bioprinting Inkjet Nozzles Based on Internet of Things - Priyanka, J.; Poorani, T. R.; Ramya, M. (Indian Journal of Information Sources and Services, 2023)
In the realm of 3D bioprinting, the ultimate objective is the creation of functional tissue constructs, achieved through precise control of inkjet performance and the ideal bioink composition. While the experimental standardization of these attributes can be time-consuming, their comprehension is facilitated through simulation analysis. In this paper, we use COMSOL Multiphysics to compare the rheological behaviour of three different bioprinting-friendly fluids: pure silk, silk mixed with PCL, and silk-PCL mixed with eggshell membrane. Our analysis focuses on the fluid flow dynamics in an air medium at various time intervals, specifically assessing the magnitude of velocity in each scenario. By considering both velocity and the uniformity of fluid dispersion throughout the inkjet process, we aim to identify the most advantageous fluid combination and optimal time interval for bioink applications. The transmission of this real-time data to a centralized Internet of Things (IoT) platform might facilitate the ability of researchers to remotely assess and visually represent the efficacy of various fluid combinations during the printing procedure.